Dynamics of Land Use and Land Cover Change in Bishoftu City, Oromia Regional State Ethiopia - Tsehay, Belayneh (CV. Science Tech Group, 2024)
This study investigates the land use and land cover (LULC) dynamics in Bishoftu City, Oromia Regional State, Ethiopia, The LULC analysis from 1990 to 2020 in the area reveals significant transformations in land use categories: cropland, vegetation, settlements, and wetlands. Initially, in 1990, cropland dominated the landscape, covering 76% of the total area, with vegetation at 14%, settlements at 6%, and wetlands at 4%. Over the three decades, cropland consistently decreased, dropping to 74% in 2000, 73% in 2010, and 64.7% by 2020. Vegetation cover also saw a decline from 14% in 1990 to 10% in 2020. In contrast, settlement areas increased substantially, from 6% in 1990 to 22.8% in 2020. Wetlands showed a minor but consistent reduction, decreasing from 4% in 1990 to 2.6% in 2020. These changes are predominantly driven by urban expansion, deforestation, agricultural activities, and economic development. Accuracy assessments of classified maps revealed high reliability, with overall accuracy ranging from 96% to 98%. The study highlights the urgent need for sustainable urban planning, reforestation efforts, wetland conservation, and effective land use regulations to mitigate adverse environmental impacts. In conclusion, the research underscores the critical role of understanding and addressing LULC dynamics for sustainable development. Recommendations include enhancing land use regulations, promoting sustainable agricultural practices, developing wetland conservation programs, and improving public awareness and education. This study provides valuable insights for policymakers and urban planners to make informed decisions and promotes sustainable land management practices in Bishoftu City.